Uma demonstração do teorema fundamental da álgebra - Costa, Allan Inocêncio de Souza (Universidade Federal de São Carlos, 2016)
In this work we explain an elegant and accessible proof of the Fundamental Theorem of Algebra using the Lagrange Multipliers method. We believe this will be a valuable resource not only to Mathematics students, but also to students in related areas, as the Lagrange Multipliers method that lies at the heart of the proof is widely taught.
Keywords: Polinômios; Teorema fundamental da álgebra; Multiplicadores de Lagrange; Polynomials; Fundamental theorem of algebra; Lagrange multipliers; CIENCIAS EXATAS E DA TERRA::MATEMATICA